Electrophoretic deposition of linear polyethylenimine and composite films. (August 2013) - Sun, Y; Ata, M S; Zhitomirsky, I
Abstract : Electrophoretic deposition method has been developed for the electrodeposition of linear polyethylenimine (LPEI) films. The deposition mechanism is based on the electrophoresis of protonated LPEI-H +, base generation at the cathode surface, charge neutralisation and formation of insoluble LPEI films. Quartz crystal microbalance data, coupled with the results of electron microscopy, showed that deposition rate and film thickness can be varied and controlled by the variation of deposition time and voltage. LPEI films provided corrosion protection of stainless steel substrates. LPEI was used for the dispersion, charging and electrophoretic deposition of TiO2, hydrotalcite and MnO2 particles and fabrication of composite films. Scanning electron microscopy and thermogravimetric analysis showed the formation of composite films, containing 45·4%TiO2, 53·1% hydrotalcite and 33·3%MnO2 in the LPEI matrix. The film thickness was varied in the range of 0·1–4 μm by variation of the deposition time at a constant deposition voltage. The proposed approach paves the way for the fabrication of organic–inorganic composite films combining functional properties of LPEI and inorganic materials.